AB0866 Cross-Sectional Evaluation of Vitamin D Levels in A Large Cohort of Patients with Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS). (15th July 2016) - Falcini, F.; Lepri, G.; Stagi, S.; Casalini, E.; Matucci Cerinic, M.
Abstract : Background: Vitamin D (vitD) is known for its essential role in calcium homeostasis and bone health. It is now considered as a potent neurosteroid hormone, with a pivotal role on the brain development and normal brain function. VitD ligand-receptor, a receptor that mediates the majority of vitamin D biological actions, has been found throughout the body including the central nervous system (CNS). Vitamin D deficiency is commonly observed in patients with severe mental illness such as schizophrenia. PANDAS is an autoimmune disorder characterized by obsessive-compulsive symptoms and/or tics triggered by group-A beta-hemolytic Streptococcus infections with relapsing/remitting course due to recurrence of infections itself. Despite the action of 25-hydroxyvitamin D [25(OH)D] on immune and CNS system, to our knowledge, no studies have been performed in patients with PANDAS. Objectives: To evaluate 25(OH)D levels in a large cohort of children and adolescents with PANDAS 2. To compare the results with a healthy control group. Methods: We measured plasma 25(OH)D levels in one hundred seventy-nine patients with PANDAS (49 females, 132 males, mean age at diagnosis 101.4 ±30.1 months) and an age, sex, and body mass index-matched control group of 179 subjects. Results: Patients with PANDAS showed a higher percentage of reduced 25(OH)-vitamin D levels (<30 ng/mL) in comparison with controls (94.6% vs. 82.5%; p<0.005). In addition, PANDAS patients have lower levels of 25(OH) D than controls (20.4±6.9 vs. 24.8±7.3 ng/mL, p<0.0001). This difference has been confirmed also considering the winter (13.7±3.25 vs. 21.4±5.9) and summer (21.8±6.5 vs. 32.5±8.7) period. Yet, serum 25(OH)-vitamin D levels correlated with the number of streptococcal infections before the diagnosis (p<0.005) and with their recurrences (p<0.005). Conclusions: PANDAS patients have reduced 25(OH)D values that seem to be associated with streptococcal infections, and the probability of its recurrences. So, reduced 25(OH)D levels may be a cause significantly important in PANDAS etiopathogenesis. A regular supplementation of VitD in PANDAS patients is recommended as it should improve the course of the disease and prevent or reduce the recurrences of infections and the relapses of neurological symptoms. This hypothesis should be further explored in future studies. Disclosure of Interest: None declared